The Mediating Role of Romantic Attachment in the Relationship Between Attachment to Parents and Aggression - Santona, Alessandra; De Cesare, Paola; Tognasso, Giacomo; De Franceschi, Massimo; Sciandra, Andrea (Frontiers in Psychology, 2019)
Background: A secure attachment style could promote more intimacy in romantic relationships, while an insecure attachment style could be correlated with less positive romantic relationships in adulthood. Numerous studies have noted that a secure attachment to parents was correlated with lower levels of aggression, whereas insecure attachments were associated with higher levels of aggression. We aimed to investigate the role of the attachment system as a mediator of the expression of aggressiveness during adolescence. Specifically, we considered that the attachment to parents and peers could influence one’s attachment to a romantic partner. Methods: We empirically tested whether there were relationships of parent and peer attachment on aggressiveness mediated by romantic attachment style. Participants of the study included 411 students. Results: Results indicated that for males an insecure father-child attachment style seems to be associated with higher levels of anxiety and avoidance in romantic attachments and then with aggressiveness. For females, an insecure mother-child attachment style seems to be associated with higher levels of aggressiveness. Conclusions: The attachment to parents and to peers plays a key role in defining romantic attachment according to gender, and these dimensions in turn tend to affect the levels of aggressiveness.